Meta-Analysis of the Impact of Ethnomathematics-Based Digital Learning on Students' Mathematical Understanding - Ratu Mauladaniyati; Heri Purnomo; Pradnyo Wijayanti; Sumarni Sumarni (Universitas Negeri Surabaya, 2025)
This research addresses the growing urgency to contextualize mathematics education by integrating local cultural elements through digital learning. In increasingly diverse classrooms, traditional teaching methods often fail to connect with students' cultural backgrounds, which may hinder engagement and conceptual understanding. This study aims to conduct a meta-analysis to evaluate the influence of ethnomathematics-based digital learning on students' mathematical understanding. A total of 15 peer-reviewed articles published between 2015 and 2024 were systematically selected using inclusion criteria focused on empirical studies involving digital platforms and cultural content in mathematics education. The meta-analysis procedure involved coding of effect sizes and statistical synthesis using a random-effects model. The results show that integrating ethnomathematical content into digital learning significantly improves students’ conceptual understanding, mathematical connections, and critical thinking skills. Effect sizes ranged from moderate to high, indicating a meaningful impact. The novelty of this study lies in quantifying the pedagogical value of combining ethnomathematics and technology, which has not been thoroughly addressed in previous meta-analyses. These findings recommend that educators, curriculum developers, and education policymakers adopt culturally contextualized digital learning designs to enhance mathematics learning outcomes in diverse educational settings.